Comparison between Huin-neng and Martin Luther’s Religious Psychological Thought - Li Bing-quan; Du Hai-xin; Zhang Xu dong; Du Shu-jian (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Both Huineng and Martin Luther are religious reformers with great influence in the world. There are many similarities in their religious psychological thought, such as “equality of all beings”, “the bewilderment and the enlightenment in one’s mind”, “taking the cultivation of Xin as the most important”, “guidance”, and “rationalization”. However, because they are in different eras, cultures, religions, etc., their ideological differences are also very obvious, which are mainly manifested in: inside or outside, good or evil of human nature, turning suffering into pleasure currently or suffering in living for the happiness after death, no-grasping or grasping, for all beings or for oneself, without self or with self, etc.